Analysis of Hazardous and Toxic Medical Waste Management at Hospital - Handriyanto, Candra Ferdian; Permatasari, Eska Distia; Agustin, Avita Fitri; Sabrina, Salwa Dwi; Setiawati, Triya Amanda; Adji, Irhamsyah; Septian, Ahmad Dwi (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2026)
Hospital X in Surabaya generates various types of hazardous and toxic (B3) medical waste that pose potential risks to healthcare workers, patients, the community, and the environment. This study analyzes the B3 medical waste management process, encompassing source segregation, packaging, storage at the temporary hazardous waste storage facility (TPS B3), transportation, and final treatment by licensed third parties. The results indicate that the hospital has implemented waste management practices in accordance with applicable standards and regulations, supported by auxiliary systems such as a 3R temporary storage facility (TPS 3R) for non-B3 waste and a wastewater treatment plant (WWTP) for liquid waste. Nevertheless, enhanced personnel training and strengthened monitoring are still required to ensure more optimal waste management performance.